PREVALENCE OF ASYMPTOMATIC SIGNIFICANT BACTERIURIA IN PATIENTS WITH DIABETES MELLITUS (Iraqi Journal of Medical Sciences, 2004)
Background: There are views that urinary tract infections are more common in diabetic patients but remain contentions because of varying study designs and end point. Objective: This study was to assess the prevalence of significant bacteruria among diabetic patients with no urinary symptoms. Subjects & Method: One hundred urine samples from diabetic patients (54 from patients with non insulin dependant diabetes mellitus (NIDDM), 46 from patients with insulin dependant diabetes mellitus (IDDM) and 80 urine samples from non diabetic control persons in an out patient clinic were screened for significant bacteriuria (³105 colony forming unit/ ml). Results: Nine percent (9%) of diabetic samples had significant bacteriuria (7=females and 2=males) while 2(2.5%) (both = females) of non diabetic samples had significant bacteriuria of those diabetics with significant bacteriuria 5(55.5%) were from NIDDM group and 4(44.5%) were from IDDM. Conclusion: Analysis of the results showed significant high prevalence of significant asymptomatic bacteriuria in diabetic patients compared with non diabetic patients, (P value